LITERASI DIGITAL, MENDIDIK ANAK DI ERA DIGITAL BAGI ORANG TUA MILENIAL - Nur Ika Fatmawati; Ahmad Sholikin (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
The birth of a digital knowledge-based community brought about major changes in everything. In particular, educational problems become very diverse with greater responsibilities. This requires the expertise of parents and teachers to implement appropriate solutions to various problems and also requires the ability to adapt to environmental changes. These changes require a new orientation in education, namely education that emphasizes search-and discovery-centered, learning that emphasizes creativity, initiative, and communication and cooperation. In the digital age, teachers and parents are needed who are able to keep up with the times, can play various roles as carriers of change, digital networkers, learning consultants; who have a high sense of humanity and morals, and social sensitivity, and rational and honest thoughts, so that they are able to work well in a dynamic educational environment. This article discusses several new reorientations of learning that are thought to influence vision, responsibility, social sensitivity and logical ability, and honesty. All of this leads to a reorientation to the new role of parents, namely as agents of change, knowledge renewal, and learning consultants.